Modelling and Measuring Dielectric Constants for Very Thin Materials Using a Coaxial Probe - You, K. Y.; Abbas, Z.; Lee, C. Y.; Malek, M. F. A.; Lee, K. Y.; Cheng, E. M. (Společnost pro radioelektronické inženýrství, 2014)
This paper is focused on the non-destructive measurement of the dielectric constants (relative permittivities) of thin dielectric material (0.1 mm – 0.5 mm) using an open-ended coaxial probe with an outer diameter of 4.1 mm. Normalized de-embedding and network error calibration procedures were applied to the coaxial probe. The measured reflection coefficients for the thin samples were taken with a vector network analyzer up to 7 GHz, and the calibrated reflection coefficients were converted to relative dielectric constant using an empirical reflection-coefficient model. The empirical model was created using the regression method and expressed as a polynomial model, and the coefficients of model were obtained by fitting with the data using the Finite Element Method (FEM).
Keywords: Relative effective permittivity; one-port calibration; measured reflection coefficient; open-ended coaxial probe; thin dielectric substrate